Comprehensive mucoadhesive study of anionic polymers and their derivate. (August 2017) - Laffleur, Flavia; Netsomboon, Kesinee; Bernkop-Schnürch, Andreas; Westmeier, Dana; Stauber, Roland H.; Docter, Dominic
Graphical abstract: Highlights: Anionic polymers were modified with sulfhydryl bearing ligands to evaluate their mucoadhesiveness. Mucoadhesion augmented up to 59.23-fold compared to corresponding unmodified polymer. Tensile strength, bioadhesion, rotating cylinder and consolidation assay were performed on buccal tissue. Abstract: Aim: The purpose was to compare the mucoadhesive properties of well-known anionic polymers such as alginate (AL), carboxymethyl cellulose (CMC), polycarbophil (PC) and hyaluronic acid (HA) with regards to potential improvement in mucoadhesiveness based on chemical modification. Methods: AL, CMC, PC and HA, respectively, were modified with sulfhydryl groups of cysteine (CYS) on their polymeric backbone via amide bond formation. Viability and safety was evaluated on mucosal surface. Histology imaging was taken via H&E staining. Intense mucoadhesive studies were performed on mucosal tissue determining residence time, adhesion and total work of adhesion as well as maximum detachment force of unmodified and modified polymers, respectively. Results: Both polymers, unmodified anionic and modified ones, exhibit no toxicity at all. Histology imaging was in good agreement with the viability study on the mucosal surface. Unmodified anionic polymers reveal limited mucoadhesiveness whereas modified polymers showed up to 2.18-fold, 2.77-fold, 16.29-fold and 59.23-fold more pronounced total work of adhesion in case of CMCCYS, HACYS, PCCYS and ALCYS, respectively. Conclusion: This comprehensive study provides deep understanding for the appropriate choice of mucoadhesive excipient for the development of mucosal drug delivery systems.